2006
DOI: 10.1111/j.1600-065x.2006.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine natural killer cells: a specialized differentiation regulated by ovarian hormones

Abstract: In adult females of many species, a transient population of natural killer (NK) cells appears in cycles within the uterine endometrium (lining). Appearance of these lymphocytes coincides with specific phases of the ovarian hormone cycle and/or early pregnancy. Studies in rodents, women, and pigs dominate the literature and suggest the uterine (u)NK cells are an activated subset sharing many but not all features with circulating or lymphoid organ-residing NK cells. During successful murine pregnancy, uNK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(57 citation statements)
references
References 248 publications
(273 reference statements)
1
48
0
Order By: Relevance
“…They are either derived by in situ proliferation of tissue-resident NKC precursors or recruited from the circulation (71). Transplantable uNKC progenitors have been identified in primary and secondary lymphoid tissues but not in uterine segments (71). This observation is consistent with the scenario that the few uNKC detected at early pregnancy implantation sites were recruited from the circulation, lymph nodes, or BM and proliferated massively in the decidua, generating the large number of uNKC seen at midgestation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…They are either derived by in situ proliferation of tissue-resident NKC precursors or recruited from the circulation (71). Transplantable uNKC progenitors have been identified in primary and secondary lymphoid tissues but not in uterine segments (71). This observation is consistent with the scenario that the few uNKC detected at early pregnancy implantation sites were recruited from the circulation, lymph nodes, or BM and proliferated massively in the decidua, generating the large number of uNKC seen at midgestation.…”
Section: Discussionsupporting
confidence: 74%
“…uNKC deficiencies were previously found in IL-15 Ϫ/Ϫ mice that have residual amounts of improperly developed NKC (71) and in IL-11 Ϫ/Ϫ or Hoxa-10 Ϫ/Ϫ mice bearing developmentally impaired deciduae (72,73). However, T-bet Ϫ/Ϫ mice that have an overall reduction in NKC number do contain normal numbers of uNKC (71). Thus, although the general NKC phenotype of Runx3 Ϫ/Ϫ mice is significantly milder than that of IL-15 Ϫ/Ϫ mice, both mouse strains completely lack uNKC, underscoring the important role of Runx3 in IL-15-mediated signaling in NKC development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have found that myeloid CD11c+ cells, myeloid GR1+ cells including monocytes and NK cells represent the 3 major cell types in a pregnant uterus. They were most probably drawn at the sites of implantation to mature and proliferate locally as shown by J. Pollard’s group for macrophages [45] and A. Croy’s laboratory for major roles played by uterine NK cells [29], [46][49].…”
Section: Discussionmentioning
confidence: 97%
“…These cells can be found in the decidua during the implantation and are activated in day seven of pregnancy (39). Regarding the periodical changes of NK cells, it seems that they are under the control of the ovarian hormones (40,41). NK cells play a fundamental role during the first stages of pregnancy, as the secretory factors of these cells are considered as the regulatory mediators in the expression of vascular tissue genes, decidualization reaction and survival of pregnancy; however, increase in the number of NK cells leads to an increase in abortion (8,13,15,19,42).…”
Section: Discussionmentioning
confidence: 99%